المعدول به عن القياس عند المالكية -دراسة تأصلية تطبيقية - مجوري, ابراهيم (University of eloued جامعة الوادي, 2021)
"هذا البحث الـمـوسوم بـــــ: ""المعدول به عن القياس عند المالكية دراسة تأصيلية تطبيقية"" إشكاليته الأساسية ماهي: المضامين والدلالات التي يحملها المعدول به عن القياس عند المالكية تأصيلا وتطبيقا؟ حاولت الدراسة الإجابة عنها، من خلال ثلاثة مباحث: أحدهما: تأصيلي، والآخران: متعلقان بالجانب التطبيقي. تناول المبحث الأول الإطار المفاهيمي، من خلال الوقوف على حقيقة المعدول به عن القياس؛ ببيان مفهومه، وصوره، والكشف عن علاقته ببعض المباحث الأصولية. ثمّ الإطار المتعلق بالأحكام فقد تمّ التطرق إلى حكم القياس على المعدول به عن القياس، دراسة أصولية مقارنة، والتّكييف الأصولي ،من خلال بيان حكم إطلاق الثابت على خلاف القياس ،والدلالة الأصولية التي حملت علماء المالكية على القول به. أمّا المبحث الثاني والثالث: فيتضمن الجانب التطبيقي من الدراسة ،عُنِيتُ فيه باختيار نماذج ؛تبيّن منهج المالكية في تعاملهم مع المسائل المعدول بها عن القياس في العبادات، وأخرى في المعاملات. توصّلت الدراسة إلى جملة من النتائج، لعل أهمها أنّ المعدول به عن القياس، ضرب من ضروب الاجتهاد المالكي، يجمع فيه المجتهد بين القاعدة الكلية والدليل الجزئي، فإذا تعذّر الجمع، صار إلى الترجيح، كما أوصت الدراسة بتوسيع البحث ؛ليشمل جميع المذاهب الفقهية ؛للوصول إلى نظرية فقهية، تجمع شتات الأحكام الاستثنائية ""Research Summary This research is titled, Al-Ma’dul bihi ‘an al-Qiyas ‘ind al-Malikiyah: Dirasah Ta’siliyah Tatbiqiyah (Diverting From Legal Analogy in the Maliki School: Theory and Application). The main question of this research relates to the nature and connotations of the concept of Al-Ma’dul bihi ‘an al-Qiyas, or diverting from Qiyas (legal analogy) according to the Malikis, in both theory and application? This study attempts to answer this question in three chapters: one of them theoretical and the other two applied. The first chapter deals with the conceptual framework examining the reality of diverting from Qiyas, by explaining its concept, its manifestations, and areas that overlap with topics of usul al-fiqh, such as istihsan, rukhsah (concessions), and conflict between khabar wahid (solitary narrations) and Qiyas, leading up to discussions on the main objectives of diversion from Qiyas. This provides a complete conceptual framework for both terminology and meaning. As for what relates to legal rulings, the research discusses the ruling of using analogy based on rulings that come under Al-Ma’dul bihi ‘an al-Qiyas. It provides a comparative usul study and clarifies the ruling, from an usul al-fiqh perspective, of using that which has diverted or opposed Qiyas as a principle, while considering the reasons that led the Maliki scholars to adopting it. This is then concluded by discussing this concept in light of the conflict of evidence, thus presenting a clear understanding and ruling. As for the second and third chapters, they include the practical aspect of the study, in which I collected samples of issues that oppose analogy according to the Malikis in both worship and transactions. The carefully chosen samples were based on their relevance and appropriateness to the theoretical discussion. The study arrived at several conclusions, with perhaps the most important of which is that deviation from Qiyas is a form of ijtihad, in which the jurist combines both general rule (qa’idah kuliyah) and partial evidence (dalil juz’i). If this combination is not possible, tarjih (weighing between evidence) is resorted to. The study also recommended expanding this research to include all schools of jurisprudence to arrive at a jurisprudential theory that gathers the exceptional rulings scattered in the legal tradition. "
مذكرة ماستر
Keywords: المعدول به عن القياس - المالكية - الأقوال- التأصيل- التفريع-; What is taken from analogy - Maalikis - sayings-Rooting - Branching